'The grievous mistakes of the Vanikoro concession': The Vanikoro Kauri Timber Company, Solomon Islands, 1926-1964. (1st August 2000) - Bennett, J.A.
Abstract : The British Solomon Islands Protectorate government, in the 1910s, encouraged logging operations on Vanikolo in order to diversify the economy and extend government control in the easternmost islands. The Vanikoro Timber Company began operations in 1926 without any reforestation clause included in its licence. Problems with the assessment of royalties on trees felled in the 1930s drew the attention of the Colonial Office to this. Little could be done to change the original agreement, but the British administration halted any major extension of logging until a Forestry Department could oversee a sustainable extraction regime, including reforestation, in the 1960s. The logging company, working under difficult conditions in an isolated area, was never a financial success and finally closed in 1964 when cheaper timbers became readily available on the Australian market. The Vanikolo people remained ambivalent towards the company, valuing its presence as a pathway to the wider world, but often resisting extension of its demands on the island's resources.